Cell Sheet Engineering in Periodontology: A Review - Ruchita Tejrao Patil; Prasad V Dhadse; Shrishti Salian (Journal of Clinical and Diagnostic Research, 2024)
Cell sheet engineering has developed its own place for the regeneration of tissues. It focuses on phenomena occurring at the cellular level, whereas regenerative medicine and tissue engineering aim to create or stimulate new tissue for the treatment of disease. In medicine and dentistry, tissue engineering, cell-based therapies, and regenerative medicine have been progressing rapidly for regeneration procedures. It has emerged as a promising strategy for scaffold-free cell-based regenerative medicine therapy by means of transplantable single or multi-layered cell-dense sheets to achieve tissue repair and regeneration. Cell sheet engineering could be one of the procedures for regeneration of periodontal tissues, which can yield better results. In this review, the authors will highlight the principal techniques of cell sheet engineering and its application in tissue regeneration in periodontal therapy.